(3TQM GdgOGjI GdCKjQjIs - (3GdMSjfj GdnerjnHPj, bGVj ejQ, MSjf Hf eYjf GdOjf, J (B910 (3g`s ((3eMeO LYaQ Hf YHO GdeMSfs)
(3ChdgG (B:s
(3GdgOGjI CeQ ef dOjg hcd TjA jYhO Edjg(B...(3hHYO jbhd(B...(3GdejHOj(B...(3deG QCjJ ceGd Yjf GdCYjGf hgh Yjf GdEfSGf HGdGQJbGA Edi CYdGe GdaWfI(B...s
(3BNQgG (B:s
(3hef CQGO GdGSJbUGA aj GdMceI hGdhbha Ydi ePGgH GdMceGA adjQLY Edi cJGHfG GdeSei HRHOI GdCSQGQ(B...s
(3JHUQI GdeDda (B:s
(3CQN dhaGJg aj GdPQjYI HSfI (B911(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B:(3L(B1(3,U(B316s
(3GdPQjYI(B:(3L(B6(3,U(B102(3, JMJ Qbe(B753s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs